The PPAT Legal Protection against Letters of Validity and Correctness of Documents in Registration of Electronic Mortgage Rights - Zulfikar, Mochamad Adhia (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2023)
This study aims to determine and analyze the legal protection for PPATs against Statements of Legality and Truthfulness of Documents in the registration of Electronic Mortgage Rights and to know and analyze the legal consequences for PPATs of making Statements of Legality and Truth of Documents in registration of Electronic Mortgage Rights. This research method uses a normative juridical approach, analytical descriptive research specifications, secondary data collection methods and qualitative data analysis research methods. Based on the research it was concluded that PPAT as a profession is a legal subject who needs to get legal protection in order to get a sense of security in carrying out his position to carry out the authority given by the state. Permen ATR/KBPN Number 5 of 2020 requires PPATs to attach a Statement of Validity and Document Validity, which is felt to be burdensome for PPATs in carrying out their profession because there is no legal protection that provides a sense of security for PPATs in relation to criminal and civil responsibilities imposed by the Statement of Legality and Document Authentication. The PPAT in carrying out its duties adheres to the principle of responsibility based on error (based on fault of liability), where a PPAT must be responsible for the deed as long as the mistake or violation that occurs is intentional by the PPAT. In the event that the PPAT does not know if the document provided turns out to be fake,Keywords: Electronic; Mortgage; Statement.